Kemenangan Noor Ishmatuddin 2024: Politik Identitas di Daerah Perairan Banyuasin - Al Hadar, Syahziar; Amaliatulwalidain , Amaliatulwalidain; Isabella , Isabella (Penerbit Goodwood, 2025)
Purpose: This study examines the influence of Bugis ethnic identity on Noor Ishmatuddin’s victory in the 2024 Legislative Election in the coastal areas of Banyuasin. Methodology/approach: The research was conducted in Telok Payo and Muara Sungsang, Banyuasin, using a qualitative case study approach. Data were collected through observations, interviews, online questionnaires (Google Forms), and documentation. Informants included Noor Ishmatuddin, community leaders, local residents, and campaign team members. Results/findings: Bugis ethnic identity strengthened Noor Ishmatuddin’s symbolic legitimacy; however, his electoral victory was primarily driven by inclusive campaign strategies, effective use of social media, and strong supporter loyalty. The influence of family, local strongmen, and cultural activities further enhanced voter trust without generating polarization. Conclusions: Noor Ishmatuddin’s victory in Banyuasin was not solely determined by his Bugis ethnic identity but was also shaped by inclusive campaign strategies, digital engagement, loyal grassroots support, and the involvement of family and local figures. While ethnic identity functioned as symbolic capital, the decisive factors were adaptive and participatory approaches that successfully avoided social polarization. Limitations: The study is limited to two villages, which may not fully capture broader regional dynamics. Contribution: This research enriches the understanding of identity politics in local elections and provides insights into ethical campaign strategies for multicultural regions.